THE INVENTORY KINDS OF THE TREE IN TOURISM FOREST DUMAI - Defri Yoza (Jurnal Ilmu Ilmu Kehutanan, 2017)
Inventaritation of forest is one of the activity to collect the data and information about forest resources, the potention of forest diversity also the environment as completely include of survey about statute and phisicly condition of forest, flora and fauna, human resources also the economic social condition of society arround of forest. The activity of inventaritation forest aim to identify the kinds of flora and fauna that include arround of the ecotourism forest dumai to analyze the rich of flora and fauna arround of tourism forest dumai. The result of this reseacrh showed that the category of forest like pit forest (wet) and dry forest with the position higher than pit forest located arround of river and home stay. Pit forest is one of the forest that have high volume of water it’s influenced by the rain. Revitalitation area needs to clearly the location of tourism forest dumai and revitalitation of the environment as the holistic towards of tourism forest dumai area. The society have control to participate as directly in arround of the tourism forest, there fore the guidence program and empowering society to keep the forest stand. At the plot of the observation to tree level dominate by kinds of mahang (Macarangatriloba), medang (Litsea sp.) and the kinds of meranti (Shorea sp.). the diversity of species , frequency species and dominate of species by Macaran gatriloba with the higher INP (75,68%) followed by the kinds of Litsea sp and endosperm mummalaccensis.